Analysis of the Adoption of Digital Wallet Technology in Indonesian Society - Pramusinta Septi Isnaini; Siti Jamilah (Universitas Muhammadiyah Jakarta, 2025)
Due to changes in consumer behavior and the development of technology, the acceptance of digital signage in Indonesian society has increased significantly in recent years. This study, focusing on variables such as self-efficacy, perceived usefulness and perceived ease of use, intention to use, substance norms, self-creation, and actual system usage, examines the factors that influence the adoption of virtual screen technology. The data were collected qualitatively through questionnaires distributed to the Indonesian mobile app users, and a semi-structured meta-analysis (SEMPLS) was used to analyze the samples. The results of this study show that consumer intentions are governed by perceived usefulness and ease of use, and religiosity is a moderating factor. Furthermore, self-efficacy, intention to use, and actual system use were not significantly influenced by anxiety.